PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII UPTD SMP NEGERI 5 KUPANG TENTANG SISTEM PEREDARAN DARAH - Fajriani Kirutang; Mbing Maria Imakulata; Andam S. Ardan (SINERGI : Jurnal Riset Ilmiah, 2026)
This research was conducted on May 22 and May 27, 2025, at UPTD SMP Negeri 5 Kupang. The study aimed to determine the impact of implementing the Problem-Based Learning (PBL) model on the learning outcomes of Grade VIII students at UPTD SMP Negeri 5 Kupang regarding the circulatory system. The research employed the Classroom Action Research (CAR) method developed by Kemmis and McTaggart, carried out in cycles comprising four stages: planning, acting, observing, and reflecting. The subjects of the study were 30 Grade VIII students. Data collection techniques included observations of teachers and students, evaluation test results, and documentation. The results indicated an improvement in student learning outcomes regarding the circulatory system topic. Observations of student activity showed a rise from a 69.64% score (rated "sufficient") in Cycle I to 84.82% (rated "excellent") in Cycle II, indicating success. Teacher observation scores also improved, rising from 75.75% in Cycle I to 86.36% (rated "good") in Cycle II. Regarding test results, Cycle I showed that out of 30 students, 11 met the mastery criteria (33.00% class mastery), while 19 did not (66.33%). An improvement was observed in Cycle II, where 24 out of 30 students met the mastery criteria (80% class mastery), while 6 did not (20%). Based on the results of the Cycle II assessment, the students were deemed to have achieved mastery, as a significant number met the criteria for attaining the learning objectives; therefore, conducting a subsequent research cycle was unnecessary.